2019
DOI: 10.1021/acs.analchem.9b02749
|View full text |Cite
|
Sign up to set email alerts
|

AND-Logic Based Fluorescent Probe for Selective Detection of Lysosomal Bisulfite in Living Cells

Abstract: Sulfur dioxide (SO 2 ) plays significant roles in regulating cell apotosis and inflammation. However, there are complex interactions between small biomolecules in cells, and the identification of these coexisting biomarkers remains a challenge. Herein, we report an AND logic gate based fluorescent probe (NY-Lyso), operating by responding to pH differences between organelles in cell and selectively reacting with bisulfite (HSO 3 − ). This approach allows the fluorescence of the probe to remain silent under neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 51 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…Initially, the cytotoxicity of the sensor H-HPMO was investigated with the MTT assay. 41 As shown in Figure S15 in the Supporting Information, the cell viability remained above 77% even when the cells were treated with H-HPMO with a concentration of 75 μM for 24 h. The IC 50 value was calculated to be 273.6 μM by GraphPad Prism 8 software (Figure S16 in the Supporting Information), which further indicated that H-HPMO had low cytotoxicity against PC-12 cells. Then, PC-12 cells were incubated with H-HPMO (10 μM) for 30 min at 37 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Initially, the cytotoxicity of the sensor H-HPMO was investigated with the MTT assay. 41 As shown in Figure S15 in the Supporting Information, the cell viability remained above 77% even when the cells were treated with H-HPMO with a concentration of 75 μM for 24 h. The IC 50 value was calculated to be 273.6 μM by GraphPad Prism 8 software (Figure S16 in the Supporting Information), which further indicated that H-HPMO had low cytotoxicity against PC-12 cells. Then, PC-12 cells were incubated with H-HPMO (10 μM) for 30 min at 37 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…To further demonstrate the practical utility of the sensor in biological samples, a bio-imaging experiment was carried out in living cells of PC-12 (Figure ). Initially, the cytotoxicity of the sensor H-HPMO was investigated with the MTT assay . As shown in Figure S15 in the Supporting Information, the cell viability remained above 77% even when the cells were treated with H-HPMO with a concentration of 75 μM for 24 h. The IC 50 value was calculated to be 273.6 μM by GraphPad Prism 8 software (Figure S16 in the Supporting Information), which further indicated that H-HPMO had low cytotoxicity against PC-12 cells.…”
Section: Resultsmentioning
confidence: 98%
“…These probes were normally designed based on the HSO3 --triggered recognition reactions, 38 such as nucleophilic addition with ketone or aldehyde groups, [39][40][41][42] glyoxal mono-hydrazone, 43 and other Michael-type additions. [44][45][46][47][48] Nevertheless, there are still some tough issues that need to be addressed for bisulfite detection in practical food samples, especially those with high background autofluorescence signals.…”
Section: Introductionmentioning
confidence: 99%
“…Counter is one of the fundamental sequential logic circuits, whichh as been widely employed in frequency division, calculation of stimuli pulses, timing, and arithmetic operations. [11] To construct an analogueo fe lectronic countera tt he molecular level, we believed three issues should be considered:1 )multichannelc ompatibility;2 )transformations among different output channels triggered by the same stimulus but different amounts; and 3) availability of chemical or biochemical pairs with opposite effectst or ealizeb oth the cumulatinga nd descendingf unctions. Satisfactorily meeting all the criteria is so laboriousthat there are few reports on the construction of molecular counters.…”
Section: Introductionmentioning
confidence: 99%